ATENÇÃO FARMACÊUTICA NA ADMINISTRAÇÃO DE MEDICAMENTOS VIA SONDA ENTERAL: ESTUDO DE CASO - Corrêa, Jéssyca B.; Wirzbicki, Dieine C. d. M.; Cavinatto, Aline W.; Molin, Gislaine T. D.; Colet, Christiane d. F.; Oliveira, Karla R. d. (Salão do Conhecimento, 2013)
Resumo